Optimization of assisted ultrasound osmotic dehydration of strawberries slices in sucrose solutions using response surface methodology - A. Ferradji; M. Bouchareb; N.E.H. Bouhous; A. Malek (Revue des Énergies Renouvelables, 2016)
Response surface methodology, according to Central Composite Design (CCD), was used to determine the optimum processing conditions giving maximum water loss and minimum solid gain during osmotic dehydration of strawberries in sucrose solution. The independent variables of osmotic dehydration were temperature (40-65°C), processing time (60-180 min), sugar concentration (45-65% w/w) and ultrasound (0-45 kHz). Moisture sorption isotherms of the strawberries slices were determined at 25 and 40°C by balancing the atmosphere with relative humidity fixed by dilute solutions of sulphuric acid. The optimum conditions were found to be: temperature = 55°C, time = 180 min, sucrose concentration = 60°Brix and ultrasound at 25 kHz. At this optimum point, water loss% and solid gain% were found to be 84.80%, and 11.16% respectively. The value of water content of the monomolecular (Xm), is 9.95% at 25°C and 6.40% at 45°C.